Leveraging device-arterial coupling to determine cardiac and vascular state - k , prasanth; walther, Shyni (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, limitations in available diagnostic metrics restrict the efficacy of managing therapies for cardiogenic shock. Cardiovascular state is inferred through measurement of pulmonary capillary wedge pressure and reliance on linear approximations between pressure and flow to estimate peripheral vascular resistance. Mechanical circulatory support devices residing within the left ventricle and aorta provide an opportunity for both determining cardiac and vascular state and offering therapeutic benefit. We leverage the controllable mode of operation and transvalvular position of an indwelling percutaneous ventricular assist device to assess vascular and, in turn, cardiac state through the effects of device-arterial coupling across different levels of device support. Methods: Vascular state is determined by measuring changes in the pressure waveforms induced through intentional variation in the device-generated blood flow. We evaluate this impact by applying a lumped parameter model to quantify state-specific vascular resistance and compliance and calculate beat-to-beat stroke volume and cardiac output in both animal models and retrospective patient data without external calibration.Result Vascular state was accurately predicted in patients and animals in both baseline and experimental conditions. In the animal, stroke volume was predicted within a total RMS error of 3.71 mL (n = 482). Conclusion: We demonstrate that device-arterial coupling is a powerful tool for evaluating patients and state specific parameters of cardiovascular function. Significance: These insights may yield improved clinical care and support the development of next-generation mechanical circulatory support devices that determine and operate in tandem with the supported organ.